The effect of compensation on satisfaction and employee performance - Darma, Prayoga Setia; Supriyanto, Achmad Sani (MEC-J (Management and Economics Journal), 2017)
The globalization era requires employees to have good performance and results. Therefore, many companies implement compensation system. Effective compensation is expected to add value to employee’s satisfaction to stimulate employees to always work better. This research aim is to determine the effect of compensation on employee satisfaction and employee performance and employee satisfaction to mediate the effect of compensation on employee performance. The research objects are employees of PT. Telekomunikasi Indonesia. The data is collected by questionnaires and analyzed by SmartPLS version 2.0M3 software. The results show that compensation effects on employee satisfaction and employee performance at PT. Telekomunikasi Indonesia. Employee satisfaction can mediate the effect of compensation on employee performance. It can be concluded that compensation at PT. Telekomunikasi Indonesia has been classified as good and can improve employee satisfaction and employee performance.Keywords: Compensation, Satisfaction, Employee Performance